Transposon tagging of genes for cell-cell interactions in Myxococcus xanthus. - Kalos, M (1990)
The prokaryote Myxococcus xanthus is a model for cell interactions important in multicellular behavior. We used the transposon TnphoA to specifically identify genes for cell-surface factors involved in cell interactions. From a library of 10,700 insertions of TnphoA, we isolated 36 that produced alkaline phosphatase activity. Three TnphoA insertions tagged cell motility genes, called cgl, which control the adventurous movement of cells. The products of the tagged cgl genes could function in trans upon other cells and were localized primarily in the cell envelope and extracellular space, consistent with TnphoA tagging genes for extracellular factors controlling motility.